Meanings and pedagogical value of active methodologies. An expert view from Physical Education - León- Díaz, Óscar; Martínez-Muñoz, Luis Fernando; Santos-Pastor, María Luisa (Revista Complutense de Educación, 2022)
Introduction. In recent times, there is a proliferation of research and experiences on the application of new teaching-learning approaches focused on the development of key competences. However, there is no consensual conceptual, terminological and procedural framework on what this type of methodological proposals implies in practice. Our study aims to analyze the existing theoretical conceptions on active methodologies in Physical Education. Method. The research has used the Delphi method to consult experts in the field. A total of 25 teachers from the national level specialized in Physical Education have participated. Results. The main findings of the research have made it possible to elaborate a theoretical and conceptual map of the active methodologies in Physical Education, highlighting their potential to favor skills learning in students. Discussion Experts agree on the possibilities they offer to achieve greater adaptability, linkage and transfer of school practices to the current educational and social reality. It is concluded that the use of these methodologies is not only a desirable but achievable challenge.